ANALISIS PETROFISIKA DAN PENYEBAB LOW RESISTIVITY RESERVOIR ZONE BERDASARKAN DATA LOG, SEM, XRD DAN PETROGRAFI PADA LAPANGAN X SUMATERA SELATAN - Rita Aprilia; Ordas Dewanto; Karyanto Karyanto; Aldis Ramadhan (Jurnal Geofisika Eksplorasi, 2018)
Hydrocarbon reservoir zone located on Low Resistivity is a typical and hidden oil and gas layer which always wrong in assessing as a water layer due to the complex geological origin and resistivity log limitation in identifying hydrocarbon. Presence of shale in a reservoir will decreasing resistivity value and increasing saturation value, so it can cause the results of the analysis to be pessimistic in the identification of hydrocarbons. In that case need to do analysis to core data on research area in order to know the cause of Low Resistivity on reservoir zone that having a probability of hydrocarbon content. Reservoir zone that has low resistivity value is at depth 1572-1577 mD. In this zone, it has a low resistivity value around 2.7- 4.4 ohm-m, with water saturation value around 47%-74% which causes on Low Resistivity reservoir zone to be between hydrocarbons and water reservoir zone. Then, on this research, Low Resistivity is also caused by Lamination Clay of shale type presence which consists of several types of Clay which can cause reservoir zone is at low resistivity value. This Clay type consist of Kaolite 20%, Illite 4%, and Chlorite 4% minerals as well as the presence of other minerals as proponent of low resistivity that is Quartz 60%, Plagioclase 9% and Calcite 3% as conductive minerals.